An evaluation of the California injury and illness prevention program - Mendeloff, John M.; Gray, Wayne B. (Wayne Burger), 1955-; Haviland, Amelia; Main, Regan; Xia, Jing (Technical report (Rand Corporation), 2012)
The Injury and Illness Prevention Program (IIPP) requirement has been the most frequently cited standard in California workplace health and safety inspections almost every year since it became effective in July 1991. Every workplace safety inspection must assess compliance with the IIPP. This report presents the results of an evaluation of the IIPP's effects on worker injuries in California and should inform policy both in California and in the federal Occupational Safety and Health Administration (OSHA) program, which has made the adoption of a similar national requirement a top priority. Using data from the Workers' Compensation Information System, OSHA Data Initiative statistics, and Workers' Compensation Insurance Rating Bureau of California reports on medical and indemnity claims from single-establishment firms, the evaluation team analyzed the impact of citations for violations of the IIPP on safety performance by (1) using the number of citations as a measure of effectiveness and (2) assessing the number of establishments that were cited for noncompliance and then came into compliance. They found that enforcement of the IIPP appears to prevent injuries only when inspectors cite firms for violations of specific subsections of that standard. Eighty percent of the citations of the IIPP by the California Division of Occupational Safety and Health program are for only a different section, the one that requires employers to have a written IIPP. The specific subsections refer to the provisions that mandate surveying and fixing hazards, investigating the causes of injuries, and training employees to work safely. Because about 25 percent of all inspections cite the IIPP, citations of the specific subsections occur in about 5 percent of all inspections. In those inspections, the total recordable injury rate falls by more than 20 percent in the two years following the inspection.